Atrial myxoma surgery and P‐wave remodeling. Issue 9 (16th August 2022) - Herrera, Cristian; Bruña, Vanesa; Barrio, Jose María; Cuerpo, Gregorio; Fernández‐Avilés, Francisco; Bayés de Luna, Antonio; Martínez‐Sellés, Manuel
Abstract: Introduction: Data regarding atrial electrocardiographic parameters in patients with atrial myxomas are scarce. Methods: We aimed to study atrial electrocardiographic features in patients with atrial myxomas, before and after surgery. We also analyze the incidence of atrial fibrillation during follow‐up and its correlation with different P‐wave indexes. In total 32 patients in sinus rhythm that underwent atrial myxoma surgery were included. Results: Mean age was 55.0 ± 12.6 years and 18 (56.3%) were women. Ten patients had left atrial enlargement (31.3%). Only one myxoma was located in the right atrium. At baseline seven cases of partial interatrial block (IAB) were detected (21.9%), two in the absence of left atrial enlargement. There were significant differences in atrial electrocardiographic indexes before and after surgery, including P‐wave duration (108.9 ± 17.9 ms vs. 93.0 ± 12.4 ms; p < .001), partial IAB (21.9% vs. 3.1%; p  = .012) and duration of P‐wave terminal force in lead V1 negativity (−0.6 ± 0.3 vs. −0.5 ± 0.3 mm; p  = .034). At a mean follow‐up of 10.0 ± 5.5 years, 10 patients (31.3%) had experienced at least one episode of atrial fibrillation. Post‐operative P‐wave duration was associated with atrial fibrillation occurrence during follow‐up (Hazard ratio: 0.90, 95% confidence interval: 0.83–0.98; p = .020). Conclusions: Abnormalities in atrial electrocardiographic indexes are common in atrial myxomas and frequently improve after surgery. Post‐operative P‐wave duration is associated with atrial fibrillation occurrence during follow‐up.